2017
DOI: 10.19082/3535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Persian Medicine Remedy on Chemotherapy Induced Nausea and Vomiting in Breast Cancer: A Double Blind, Randomized, Crossover Clinical Trial

Abstract: BackgroundChemotherapy induced nausea and vomiting (CINV) is a side effect, and has negative effect on quality of life and continuation of chemotherapy. Despite new regimen and drugs, the problems still remain and standard guidelines, effective treatment and supportive care for refractory CINV are still not yet established. Persian medicine, the old Iranian medical school, offer Persumac (prepared from Rhus Coriaria and Bunium Persicum Boiss).ObjectiveThe specific objectives were to assess the effect of Persum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Bunium persicum is a perennial plant in Iran. A randomized, double blind, crossover clinical trial shows that Persumac, a combination of R. coriaria and B. persicum , may be helpful in patients with refractory chemotherapy - induced nausea and vomiting (Nazari et al, 2017 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…Bunium persicum is a perennial plant in Iran. A randomized, double blind, crossover clinical trial shows that Persumac, a combination of R. coriaria and B. persicum , may be helpful in patients with refractory chemotherapy - induced nausea and vomiting (Nazari et al, 2017 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…Outcomes showed that Persumac decreased the frequency and severity of nausea and vomiting significantly. However, in the acute phase, a reduction in the severity of nausea was not significant (Nazari et al, 2017).…”
Section: Clinical Trialsmentioning
confidence: 86%
“…Persumac is a traditional Persian medication that is made of sumac (Rhus Coriaria) and Kermani Black Zira (Bunium persicum) (Nazari et al, 2017).…”
Section: Persumacmentioning
confidence: 99%
“…In Persian medicine (PM), nausea is commonly known as "Ghathayan" that means the GI attempt to expel the substances accumulated in the stomach, without success, and vomiting is known as "Ghey" means GI motility in order to repel the accumulated substances through the mouth successfully [3]. Both of these definitions are corresponding to the states of nausea and vomiting in modern medicine [4]. According to the holistic viewpoint of PM, the human body is made up of four main substances called "Humor" (Khelt), each of which has a unique temperament (Mizaj), and, on the basis of temperament, they play certain roles in the body.…”
Section: Dear Editormentioning
confidence: 99%
“…Comparison of the structural and functional properties between abnormal yellow bile and free radicals, which produce by chemotherapy agents and cause GI mucosal layer damage, reveals similarities as shown in Table-1. It seems that free radicals are considered to be a kind of abnormal yellow bile GMJ.2019;8:e1412 www.gmj.ir in PM [4]. On the other hand, In PM viewpoint, important organs have close physiological links and interactions with each other, so that the health and illness of each one can directly affect another.…”
Section: Dear Editormentioning
confidence: 99%